Feeding behaviour of Wigeon Anas penelope on variable grassland swards - Mayhew, Peter W; Houston, David C (Wildfowl, 1998)
Wigeon in winter have a specialised grazing behaviour which involves repeatedly returning to the same feeding areas of short grassland. Two experiments are described which examined their behavioural adaptations to this type of grazing. A study on captive birds showed that they exhibited highest peck rates on grass of 30 mm height and peck rates declined on both taller and shorter grassland. Wild birds were shown to concentrate their grazing on high quality fertilised grassland, through slower walking speeds and increased peck rates.